2017
DOI: 10.1002/jcb.26015
|View full text |Cite
|
Sign up to set email alerts
|

A Network Meta‐Analysis of Non‐Melanoma Skin Cancer (NMSC) Treatments: Efficacy and Safety Assessment

Abstract: The mainstream treatments for non-melanoma skin cancer (NMSC) include photodynamic therapy (PDT), surgery excision (SE), cryotherapy (CT), imiquimod (IM), radiotherapy (RT), 5-fluorouracil (FU), and vehicle (VE). Our network meta-analysis (NMA) was aimed at evaluating the efficacy and safety of these seven treatments and providing superior ones. After searching the trials from Embase and PubMed and screening with our criteria, we conducted the NMA with software R 3.2.3 and STATA 13.0. Complete lesion response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
0
17
1
3
Order By: Relevance
“…Although the literature suggests female gender correlates with poorer HRQL, our study found no correlation. Younger age (<50 years) has been a predictor of poorer HRQL in prior validation of the SCI, yet this correlation was only weakly associated across the emotional domain in bivariate and multivariate analysis …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the literature suggests female gender correlates with poorer HRQL, our study found no correlation. Younger age (<50 years) has been a predictor of poorer HRQL in prior validation of the SCI, yet this correlation was only weakly associated across the emotional domain in bivariate and multivariate analysis …”
Section: Discussioncontrasting
confidence: 99%
“…Keratinocyte carcinomas were predominately managed surgically in the Spanish population. This may reflect lower incidence and implementation of tissue‐sparing methods given surgical excision has historically been favoured regarding clearance and cure . However, in an increasingly patient‐oriented health‐care system, non‐surgical means (when amenable) should be considered and scar size and location should be prioritised as secondary outcomes following curative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…NMSCs are considered curable diseases and the treatment mostly comprises of lesion removal. In addition, systemic and topical pharmacotherapy, cryotherapy (CT), photodynamic therapy (PDT), laser, and radiotherapy (RT) are also used [ 109 , 110 , 111 , 112 , 113 ]. A variety of techniques may be employed when removing NMSC.…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
“…Ez a technika megbízható sebészi ellátást biztosít szövetkímélő módon, elfogadható gyorsasággal és kiemelkedő költséghatékonysággal (19). Egy közelmúltban megjelent meta-analysis eredményei szerint a daganat teljes eltávolítása, és a recidiva arányok tekintetében sebészi kimetszéssel sokkal jobb eredményeket lehet elérni, mint a nem sebészeti eljárásokkal (cryoterápia, fotodinámiás terápia, rtg kezelés, 5-flurouracil, és imiquimod terápia (23).…”
Section: Slow Mohs Vagy Multistage Technikaunclassified